2004
DOI: 10.1111/j.1365-2893.2004.00514.x
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in responses to interferon‐β‐1a in chronic hepatitis C unresponsive to interferon‐α: a better response in Chinese patients

Abstract: Re-treatment with interferon-alpha alone for chronic hepatitis C nonresponders to interferon-alpha monotherapy is almost ineffective. This multicentre, randomized, parallel-group, dose-finding study evaluated the efficacy of interferon-beta-1a in the treatment of chronic hepatitis C patients unresponsive to interferon-alpha. A total of 267 patients were randomized to one of four groups: subcutaneous interferon-beta-1a 12 MIU (44 microg) or 24 MIU (88 microg) administered three times weekly or daily. Patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 43 publications
(70 reference statements)
3
20
2
Order By: Relevance
“…Such finding has also been observed in IFN-α therapy. 28 Recently, Chan et al 29 strongly supported the use of IFN-β-1a as an alternative to the IFN-α for Asian patients with chronic hepatitis C. The present study was more consistent with that from Cheng et al 21 since we would expect a much better response from the treatment-naïve population. The other interesting finding in our study was the trend toward a better response for IFN-β-1a therapy in the patients with higher baseline viral load.…”
supporting
confidence: 82%
See 3 more Smart Citations
“…Such finding has also been observed in IFN-α therapy. 28 Recently, Chan et al 29 strongly supported the use of IFN-β-1a as an alternative to the IFN-α for Asian patients with chronic hepatitis C. The present study was more consistent with that from Cheng et al 21 since we would expect a much better response from the treatment-naïve population. The other interesting finding in our study was the trend toward a better response for IFN-β-1a therapy in the patients with higher baseline viral load.…”
supporting
confidence: 82%
“…Recently, two other studies using IFN-β-1a had been reported. Cheng et al 21 reported results of IFN-β-1a monotherapy in 270 patients who had HCV infection that was non-responsive to IFN-α therapy. Although the overall SVR was merely 3.4%, a sub-group analysis provided the interesting finding that Chinese population achieved a significantly higher SVR (21.7%) suggesting an ethnic factor at the work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recombinant human interferon-beta-1a and interferon-beta1b are produced in mammalian cells or Escherichia coli, respectively [57] . It was reported that recombinant human interferon-beta-1a with or without ribavirin has an excellent safety profile, and after 24-wk-treatment of recombinant human interferon-beta-1a with or without ribavirin, SVR was 21.6% and 27.4% in HCV genotype 1 and genotype 2 patients, respectively [57][58][59][60] . Peginterferonbeta-1a may be beneficial for patients infected with HCV [61,62] .…”
Section: Recombinant Interferon-betamentioning
confidence: 99%